Clinical and Arterial Spin Labeling Brain MRI Features of Transitional Venous Anomalies. Issue 3 (4th December 2017) - Zhang, Michael; Telischak, Nicholas A.; Fischbein, Nancy J.; Steinberg, Gary K.; Marks, Michael; Zaharchuk, Greg; Heit, Jeremy J.; Iv, Michael
ABSTRACT: BACKGROUND AND PURPOSE: Transitional venous anomalies (TVAs) are rare cerebrovascular lesions that resemble developmental venous anomalies (DVAs), but demonstrate early arteriovenous shunting on digital subtraction angiography (DSA) without the parenchymal nidus of arteriovenous malformations (AVMs). We investigate whether arterial spin labeling (ASL) magnetic resonance imaging (MRI) can distinguish brain TVAs from DVAs and guide their clinical management. METHODS: We conducted a single‐center retrospective review of patients with brain parenchymal DVA‐like lesions with increased ASL signal on MRI. Clinical histories and follow‐up information were obtained. Two readers assessed ASL signal location relative to the vascular lesion on MRI and, if available, the presence of arteriovenous shunting on DSA. RESULTS: Thirty patients with DVA‐like lesions with increased ASL signal were identified. Clinical symptoms prompted MRI evaluation in 83%. Symptoms did not localize to the venous anomaly in 90%. Ten percent presented with acute symptoms, only one of whom presented with hemorrhage. ASL signal in relation to the venous anomaly was identified in: 50% in the adjacent parenchyma, 33% in the lesion, 7% in a distal draining vein/sinus, and 10% in at least two of these sites. Follow‐up DSA confirmed arteriovenous shunting in 71% of ASL‐positive venous anomalies. Interrater agreement was very good ( κ = .81‐1.0, P < .001). CONCLUSION: A DVA‐like lesion with increased ASL signal likely represents a TVA with arteriovenous shunting. Our study indicates that these lesions are usually incidentally detected and have a lower risk of hemorrhage than AVMs. ASL‐MRI may be a useful tool to identify TVAs and guide further management of patients with TVAs.